Drivers of Climate Change Mitigation Strategies in the Cement Industry: An Empirical Study in India - Sachin Balsara (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Production of cement is among the high-emission and most energy-intensive industrial processes worldwide. India ranks as the second-largest consumer and producer of cement globally. Within the country, the cement sector is the second-largest contributor to greenhouse gas (GHG) emissions and the third-highest consumer of energy. These ongoing emissions significantly contribute to severe climate change. As a result, the cement industry faces increasing pressure to lower its GHG output. The purpose of this study is to investigate the major variables affecting climate change mitigation initiatives in the cement industry in India. To achieve this, the Analytical Hierarchy Process (AHP) is employed to identify and rank the main drivers behind these mitigation strategies. A systematic assessment of these factors according to their relative importance is made possible by the AHP technique.The findings of the study identified thirty key factors influencing climate change mitigation strategies and practices. The AHP analysis revealed that the most critical drivers, based on global rankings, include litigation risks, physical threats to infrastructure and supply chains, public health concerns, increasing demand for low-carbon products, customer expectations regarding environmental responsibility, scrutiny from media and societal pressure and non-governmental organizations to reduce emissions.